2006
DOI: 10.1017/s0265021505002309
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects on bispectral index of mild vs. moderate hypothermia during cardiopulmonary bypass

Abstract: Moderate hypothermic cardiopulmonary bypass has lower bispectral index scores when compared to mild hypothermic cardiopulmonary bypass, at a steady state of inspired enflurane. This may reflect an actual increase in the depth of hypnosis. However, as this study did not address the physico-chemical changes of the volatile agent or the accuracy of the bispectral index algorithm at lower temperatures, we would not advocate a change in practice based solely on this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Similarly, Bauer et al 34 found a 30% reduction in propofol infusion rates and plasma propofol concentration in their BIS-guided group during on-pump coronary artery bypass surgery. [38][39][40] However, the results of the logistic regression analysis confirm that the reduction of noradrenaline requirements correlates most strongly with the reduction in the SPC, which results from BISguided administration of sevoflurane. As the target range of BIS values was set to 40 to 60, the concentration of sevoflurane in the oxygenator fresh gas supply was not reduced when BIS values exceeded 40 and was never reduced below 0.3%.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Bauer et al 34 found a 30% reduction in propofol infusion rates and plasma propofol concentration in their BIS-guided group during on-pump coronary artery bypass surgery. [38][39][40] However, the results of the logistic regression analysis confirm that the reduction of noradrenaline requirements correlates most strongly with the reduction in the SPC, which results from BISguided administration of sevoflurane. As the target range of BIS values was set to 40 to 60, the concentration of sevoflurane in the oxygenator fresh gas supply was not reduced when BIS values exceeded 40 and was never reduced below 0.3%.…”
Section: Discussionmentioning
confidence: 82%
“…However, hypothermia during CPB has also been reported to decrease BIS values [9]; thus, the interpretation of the BIS values in the current study might require further attention. The body temperatures of the patients were kept at 35.1℃ and 35.3℃ during partial CPB, and this mild hypothermia may have caused the decreased BIS values.…”
Section: Discussionmentioning
confidence: 85%
“…The Narcotrend monitor has some advantages. It has two channels: one is used for EEG monitoring during general anesthesia, and the other to compare the statuses of two hemispheres [17][18][19][20] . Anesthesia depth monitoring with the Narcotrend monitor has no infl uence on the heart surgery in the presence of CPB, but BIS may affect the CPB.…”
Section: Discussionmentioning
confidence: 99%